Influence of Thyroid Disorders on Liver Function Tests in –Diyala Governorate - Ibrahem Jalil , Noor; S Baban , Raya; A Mahmoud , Alaa (Diyala Journal of Medicine, 2021)
Background: Thyroid diseases may disturb liver function; liver disease modulates thyroid hormone metabolism, and a range of systemic diseases disturb both organs. There are clinical and laboratory relations between thyroid and liver diseases. Patients with chronic liver disease may have thyroiditis, hyperthyroidism, or hypothyroidism.aPatients with subacute thyroiditis or hyperthyroidism may have abnormalities in liver function tests, which return to normal as the thyroid disorder improves. Objective: The present study is designed to investigate the effects of thyroid disorders on liver function tests. Patients and Methods: In this study sixty patients were employed and categorized into two groups, thirty patients with hyperthyroidism (13 male and 17female) with age range of 25-45years, (mean 33.38) and thirty patients with hypothyroidism (11male and 19 female) with age range 25-45 years (mean 36.78),while 30 normal healthy individuals were chosen as a control group (15male and 15 female) in the same age range (mean 34.44) were taken for comparison. Blood samples were collected from the patients at Baqubah Teaching Hospital , between April 2020 to July 2020. Basic serum biochemical parameters including, thyroid stimulation hormone (TSH), triiodothyronine(T3) and thyroxin (T4)were assayed for patients and control groups by Cobas e 411 autoanalyzer within eight weeks. Serum normal values for alanine aminotransferase (ALT). ALT (Alanine Aminotransferase), Aspartate aminotransferase (AST), alkaline phosphatase test (ALP), direct bilirubin (DB) and total bilirubin( TSB) were assayed within four days by Cobas integra 400 plus autoanalyzer. Results: The mean value of ALT, AST, ALP,TSB, and DB in patients with hyperthyroidism, and hypothyroidism was significantly increased when compared with their mean values of healthy control (p <0.05).A significant difference was also found in mean values of T3,T4,TSH in hyperthyroidism and hypothyroidism when compared with their mean values of healthy control(p <0.05). Results of this work revealed a significant negative correlation of TSH with ALP and TSB (p<0.05). Further, T4 showed a significant positive correlation with ALP (P<0.05).The same results revealed that there was a significant positive correlation between T3 and ALP with (p<0.05).There was no significant correlations between ALT,AST,DB with TSH,T3,T4.Further,no significant correlations between TSB and T3,T4 (p >0.05). Conclusion: The current study shows that thyroid disorder might cause significant effect on the metabolism of hepatocytes reflected by an increase in biochemical parameters of liver function test AST, ALT ALP,TSB and DB in both hyperthyroidism and hypothyroidism subjects.